2021
DOI: 10.4236/ojpsych.2021.112009
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Early Intervention Psychosis (EIP) Service Patient’s Experience of Sleep, Exercise, Sleep Hygiene Advice and Fitbit Wearable Activity and Sleep Tracker

Abstract: Background: In psychosis physical activity, sleep, mental health, physical health, wellbeing, quality of life, cognition and functioning are interconnected. People who experience psychosis are more likely than the general population to have low levels of physical activity, high levels of sedentary behaviour and sleep problems. This project was innovative in seeking to address these issues through provision of a wearable activity and sleep tracker (a Fitbit) and sleep hygiene advice. Participants: Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Prediabetes: All patients were given lifestyle modification advice, as well as offered other interventions such as walking groups and the offer to participate in our Welltrack study (use of Fitbit to improve activity and well-being). 31,32 Patients were also referred to a GP for further lifestyle modification, and one patient enrolled in the NHS Diabetes Prevention Programme. One patient participated in the Well-track study.…”
Section: Interventions Offered To Those With Prediabetes and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediabetes: All patients were given lifestyle modification advice, as well as offered other interventions such as walking groups and the offer to participate in our Welltrack study (use of Fitbit to improve activity and well-being). 31,32 Patients were also referred to a GP for further lifestyle modification, and one patient enrolled in the NHS Diabetes Prevention Programme. One patient participated in the Well-track study.…”
Section: Interventions Offered To Those With Prediabetes and Diabetesmentioning
confidence: 99%
“…In total five of six patients with diabetes had either already participated in the Well-track (Fitbit) 31,32 study or had started to participate.…”
Section: Interventions Offered To Those With Prediabetes and Diabetesmentioning
confidence: 99%
“…Basic sleep hygiene education, such as avoiding caffeine or alcohol consumption, having a specific bedroom, maintaining sleep regularity, avoiding daytime naps and stress management, has been shown to be beneficial in people with psychosis [ 4 , 45 ], particularly if coupled with a portable sleep tracker [ 46 ]. This consists of a wearable tracker (Fitbit) that can detect sleep and physical activity.…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%
“…Basic sleep hygiene education has proven to be beneficial in people with psychosis ( 11 , 46 ). In this regard, some authors demonstrated the benefits of a low cost and simple sleep intervention for early psychosis patients, consisting of sleep hygiene advice along with a provision of a wearable sleep tracker ( 86 ). Accumulated evidence has confirmed the effectiveness of the Cognitive Behavioral Therapy for insomnia (CBTi) in UHR states ( 80 , 82 , 87 ).…”
Section: Prevention and Intervention Strategies Targeting Sleep For U...mentioning
confidence: 99%